Innovation Technology : A Dictionary (2017)
Comprise definition of 1500 terms. Innovation from A to Z presents a glossary, including: Terms, older terms whose meanings have changed, acronyms, synonyms, famous names, selected abbreviations, and cross-references. A highly interdisciplinary approach incorporating strategy and entrepreneurship with technology and engineering sciences, economics, marketing, organizational behavior and theory. Ideal for engineers, managers, sales people and economists. Innovation Technology from A to Z Glossary of terms, including acronyms, synonyms, abbreviations, cross-references 1500 terms supplemented by figures and tables that clearly demonstrate the state-of-the-art in Innovation Technology